Zingiber junceum Gagnep., A New Record for the Flora of Vietnam and its Anatomical and Phytochemical Characteristics - Nguyen-Phi, Nga; Le-thi, Thu Trang; Lam, Bach Bao phuong; Nguyen, Ngoc Thuan; Van, Hong Thien (Tropical Natural History, 2025)
Zingiber junceum Gagnep. was first described in 1906 which the type specimens were collected from Angkor, Cambodia and later recorded in Laos and Thailand. In this study, Z. junceum is first recorded as an additional species for the flora of Vietnam. This species’ micro-morphological traits are described and illustrated. Furthermore, the phytochemical screening of the methanol and ethanol extracts of the different organs of Z. junceum is also provided. As a result, the rhizome and leaf shoot of Z. junceum contained some bioactive compounds such as tannin, flavonoid, alkaloid, phenolic, saponin, steroid, terpenoid, and coumarin. In contrast, the same constituents were also found in the leaf and flower extracts, except saponin. Additionally, the ethanol and methanol extracts from the different parts of Z. junceum contained significant amounts of the total triterpene, polyphenol, and flavonoid.